2002
DOI: 10.4049/jimmunol.169.8.4496
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Model of Amebic Colitis Reveals Mouse Strain Susceptibility to Infection and Exacerbation of Disease by CD4+ T Cells

Abstract: Amebic colitis is an important worldwide parasitic disease for which there is not a well-established animal model. In this work we show that intracecal inoculation of Entamoeba histolytica trophozoites led to established infection in 60% of C3H mice, while C57BL/6 or BALB/c mice were resistant, including mice genetically deficient for IL-12, IFN-γ, or inducible NO synthase. Infection was a chronic and nonhealing cecitis that pathologically mirrored human disease. Characterization of the inflammation by gene ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 45 publications
2
122
2
1
Order By: Relevance
“…Our previous study has reported an increased mast cell infiltration associated with substantially up-regulated mast cell protease genes in infected mouse ceca at 10 weeks post challenge (51). However, the fundamental question that whether mast cells contribute to parasite clearance or play a pathologic role in tissue damage remains unanswered.…”
Section: Mast Cell-mentioning
confidence: 99%
“…Our previous study has reported an increased mast cell infiltration associated with substantially up-regulated mast cell protease genes in infected mouse ceca at 10 weeks post challenge (51). However, the fundamental question that whether mast cells contribute to parasite clearance or play a pathologic role in tissue damage remains unanswered.…”
Section: Mast Cell-mentioning
confidence: 99%
“…Indeed, gene expression analysis suggests the absence of a response to amoeba in B6 mice (only 1 of 12,422 genes or expressed sequence tag was dysregulated between B6 sham-and B6 amoeba-challenged mice; data published in (9) and available at ͗https://genes.med.virginia.edu/public data/index.cgi͘). Moreover, B6 resistance does not rely on an innate proinflammatory response in that IL-12p40-deficient, inducible NO synthase-deficient, phagocyte oxidase-deficient, MyD88-deficient, or neutrophil-depleted B6 mice remain resistant (8,9).…”
Section: Resistance Of C57bl/6 Mice To Amoebiasis Is Mediated By Nonhmentioning
confidence: 99%
“…To define the host mechanisms of resistance to intestinal amoebiasis, we have used a mouse model of amoebic colitis that develops upon intracecal inoculation of trophozoites (4,8,9). A majority of CBA or C3H (either TLR4 mutant or wild-type (WT)) 3 mice develop patent infections upon challenge.…”
Section: Resistance Of C57bl/6 Mice To Amoebiasis Is Mediated By Nonhmentioning
confidence: 99%
See 2 more Smart Citations